KARAKTERISTIK ORGANOLEPTIK DAN GIZI PIE SUBSTITUSI TERIGU DENGAN TEPUNG PATI JAGUNG NUSA PENIDA (Zea mays) TERMODIFIKASI - Luh Aris Aryandeni Utami; I Nengah Sujaya (ARCHIVE OF COMMUNITY HEALTH, 2013)
The Nusa penida corn is locally produced in Nusa Penida. Corn starch, on the other hand, can be modified to produce food containing better nutrition values and overcome basic properties of natural starch that is less profitable in the production of food such as pie. Up to date, there is limited research studying the organoleptic characteristic and nutritional value of pie in Indonesia. The purpose of this study was to find the organoleptic characteristic and nutritional value of pie made from modified corn starch from Nusa Penida.This research used a simple complete random design with 5 levels of treatment of nusa penida modified corn starch (NCMS) starting from 0%, 10%, 20%, 30% and 40%, with two repetitions. The total energy from pie was measured by proximate analysis meanwhile the organoleptic characteristic was determined by preferent test.Result showed that pie produced with 20% NMCS has the highest overall acceptance and has the best taste with a score of 4.8, significantly differrent (p<0,05) with other treatments. The pie contained 429.22 kcal, but did not show significant differences (p>0,05) with other treatments. It can be concluded that the pie produced by a substitution of 20% wheat flour with NMCS was the more preferred pie by panelists.